Utilization of GPS Data of Logistic Truck as a Delivery Reporting System - Istas Pratomo Manalu; Albertinus Daniel Siahaan; Okaria Veronika Simanjuntak; Dedy Samhaz Pardede; David Calvin Tobing (Piston: Journal of Technical Engineering, 2022)
We propose a tracking system that can provide information from the truck coordinate analysis. Firstly, GSM will transmit the coordinates of the truck in real time via HTTP protocol to a website that has been hosted using shared hosting and displays a travel map on the Map Box API application. We also use MYSQL as a storage of truck coordinates. Reports will be generated after the truck arrives at the company. For system accuracy level, we set the delivery duration to the database every 10 seconds so that the generated path is closer to the original path. We compared our system with google maps to observe how accurate the system was built. The length difference of the track is 0.01 Km. The system also shows a very small deviation of starting point is 0.111322 meters and at the end point is 0.729938354 meters. While, the report contains truck ID, driver's identity, departure time, exact time, arrival time, distance, type of goods, quantity of goods, origin, destination, service, date, initial odometer, used odometer which later the results can be printed into a final report of truck usage.